Case Report: Novel Homozygous Likely Pathogenic SCN1A Variant With Autosomal Recessive Inheritance and Review of the Literature - Marco Hernández, Ana Victoria; Tomás Vila, Miguel; Caro Llopis, Alfonso; Monfort, Sandra; Martinez, Francisco (Frontiers in Neurology, 2021)
Dominant pathogenic variations in the SCN1A gene are associated with several neurodevelopmental disorders with or without epilepsy, including Dravet syndrome (DS). Conversely, there are few published cases with homozygous or compound heterozygous variations in the SCN1A gene. Here we describe two siblings from a consanguineous pedigree with epilepsy phenotype compatible with genetic epilepsy with febrile seizures plus (GEFS+) associated to the homozygous likely pathogenic variant (NM_001165963.1):c.4513A>C (p.Lys1505Gln). Clinical and genetic data were compared to those of other ten previously published patients with epilepsy and variants in compound heterozygosity or homozygosity in the SCN1A gene. Most patients (11/12) had missense variants. Patients in whom the variants were located at the cytoplasmic or the extracellular domains frequently presented a less severe phenotype than those in whom they are located at the pore-forming domains. Five of the patients (41.7%) are clinically encompassed by Dravet syndrome (DS), one of them associated acute encephalopathy. Other five patients (41.7%) had a phenotype of Epilepsy with febrile seizures plus of familial origin, while the two remaining (17%) presented focal epileptic seizures. SCN1A-related epilepsies present in most cases an autosomal dominant inheritance, however there is growing evidence that some genetic variants only manifest clinical symptoms when they are present in both alleles, following an autosomal recessive inheritance.